Atomically-thin molecular layers for electrode modification of organic transistors - Gim, Yuseong; Kang, Boseok; Kim, BongSoo; Kim, Sun-Guk; Lee, Joong-Hee; Cho, Kilwon; Ku, Bon-Cheol; Cho, Jeong Ho (ROYAL SOC CHEMISTRY, 2015)
Atomically-thin molecular layers of aryl-functionalized graphene oxides (GOs) were used to modify the surface characteristics of source-drain electrodes to improve the performances of organic field-effect transistor (OFET) devices. The GOs were functionalized with various aryl diazonium salts, including 4-nitroaniline, 4-fluoroaniline, or 4-methoxyaniline, to produce several types of GOs with different surface functional groups (NO2-Ph-GO, F-Ph-GO, or CH3O-Ph-GO, respectively). The deposition of aryl-functionalized GOs or their reduced derivatives onto metal electrode surfaces dramatically enhanced the electrical performances of both p-type and n-type OFETs relative to the performances of OFETs prepared without the GO modification layer. Among the functionalized rGOs, CH3O-Ph-rGO yielded the highest hole mobility of 0.55 cm(2) V-1 s(-1) and electron mobility of 0.17 cm(2) V-1 s(-1) in p-type and n-type FETs, respectively. Two governing factors: (1) the work function of the modified electrodes and (2) the crystalline microstructures of the benchmark semiconductors grown on the modified electrode surface were systematically investigated to reveal the origin of the performance improvements. Our simple, inexpensive, and scalable electrode modification technique provides a significant step toward optimizing the device performance by engineering the semiconductor-electrode interfaces in OFETs.
Keywords: SELF-ASSEMBLED MONOLAYERS; REDUCED GRAPHENE OXIDE; FILM TRANSISTORS; HIGH-PERFORMANCE; ELECTRICAL CHARACTERISTICS; SOURCE/DRAIN ELECTRODES; CHEMICAL-REDUCTION; PENTACENE FILMS; SURFACE; TRANSPARENT